2017
DOI: 10.1155/2017/3039817
|View full text |Cite
|
Sign up to set email alerts
|

Modelling and Interpretation of Adsorption Isotherms

Abstract: The need to design low-cost adsorbents for the detoxification of industrial effluents has been a growing concern for most environmental researchers. So modelling of experimental data from adsorption processes is a very important means of predicting the mechanisms of various adsorption systems. Therefore, this paper presents an overall review of the applications of adsorption isotherms, the use of linear regression analysis, nonlinear regression analysis, and error functions for optimum adsorption data analysis. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

30
885
1
29

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 1,953 publications
(1,110 citation statements)
references
References 66 publications
30
885
1
29
Order By: Relevance
“…The optimal bio‐adsorbent dosages were acquired before being used for this research, i.e., 3 g/L for H 2 SO 4‐ treated eucalyptus leaves and H 3 PO 4 ‐treated eucalyptus leaves and 5 g/L for eucalyptus leaves. The experimental data were used to correlate with different isotherms models like the Freundlich, Langmuir, Redlich‐Peterson, Koble‐Corrigan, Sips, Toth, Temkin, and Dubinin–Radushkevich models …”
Section: Methodsmentioning
confidence: 98%
“…The optimal bio‐adsorbent dosages were acquired before being used for this research, i.e., 3 g/L for H 2 SO 4‐ treated eucalyptus leaves and H 3 PO 4 ‐treated eucalyptus leaves and 5 g/L for eucalyptus leaves. The experimental data were used to correlate with different isotherms models like the Freundlich, Langmuir, Redlich‐Peterson, Koble‐Corrigan, Sips, Toth, Temkin, and Dubinin–Radushkevich models …”
Section: Methodsmentioning
confidence: 98%
“…It is concluded that this concentration-temperature dependence of the adsorption at equilibrium can also permit comparison between some similar experimental results realized at different temperatures. In addition, it can offer a kind of implicit dependence on temperature of different parameters used in various useful isotherm models describing adsorption [25].…”
Section: Intensification Positive Valuesmentioning
confidence: 99%
“…Over the years, a wide variety of equilibrium isotherm models (Langmuir, Freundlich, Dubinin–Radushkevich, etc.) have been presented in the literature . Langmuir isotherm adsorption is a simple and experimental model, which assumes that adsorption can only occur in a limited number of specified sites and each site can adsorb only one molecule .…”
Section: Resultsmentioning
confidence: 99%
“…The Freundlich isotherm is the earliest known relationship describing the nonideal and reversible adsorption, not restricted to the formation of monolayer. This empirical model can be applied to multilayer adsorption, with nonuniform distribution of adsorption heat and affinities over the heterogeneous surface, as in Eqn : qe=KFPCO21/nwhere K F and n are Freundlich adsorption constants that calculate the adsorption capacity . Dubinin–Radushkevich (D–R) is an experimental model used for both homogeneous and heterogeneous surfaces in adsorption processes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation